2003
DOI: 10.1046/j.1360-0443.2003.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption increases attractiveness ratings of opposite‐sex faces: a possible third route to risky sex

Abstract: Since Agocha & Cooper have shown that the likelihood of intentions to engage in risky sex increases as the facial attractiveness of the potential sexual partner increases, through the opposite-sex enhancement effect we identify a new possible link between risky sex and alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 30 publications
3
56
4
1
Order By: Relevance
“…Other studies (e.g., Jones et al, 2003;Pennebaker, 1979) have reported evidence of such an effect, though BAC was not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (e.g., Jones et al, 2003;Pennebaker, 1979) have reported evidence of such an effect, though BAC was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Participants' alcohol tolerance may have prevented BACs of .05%-.06% from causing sufficient intoxication, as further suggested by the lack of significant difference between placebo and alcohol conditions in self-reported intoxication level. Jones et al (2003) obtained attractiveness ratings for unfamiliar faces of both genders from 80 undergraduates of both genders across a range (1-6 UK units, where 1 UK unit = 8 gm Beer goggles 4 alcohol) of alcohol consumption in a campus pub. However, alcohol consumption was assessed by self-report only; BAC was not measured.…”
mentioning
confidence: 99%
“…Their hypothesis represents an inductive inference from a finding by Agocha & Cooper (1999) that the probability of having risky sex is positively associated with the facial attractiveness of the prospective sexual partner. Interestingly, Jones et al (2003) indeed found correlational evidence that individuals who had earlier ingested alcohol subsequently rated opposite-sex faces as more attractive, whereas there was no such proclivity on their parts to rate the faces as more distinctive or to rate wrist-watches as more attractive.…”
Section: A Pathway To Risky Sex?mentioning
confidence: 92%
“…Most recently, Jones and colleagues (Jones et al 2003) have suggested that alcohol intake may bolster the likelihood of engaging in risky sex by increasing the perceived facial attractiveness of potential mates. Their hypothesis represents an inductive inference from a finding by Agocha & Cooper (1999) that the probability of having risky sex is positively associated with the facial attractiveness of the prospective sexual partner.…”
Section: A Pathway To Risky Sex?mentioning
confidence: 99%
“…Stimuli consisted of 80 full color faces; 20 different faces were presented each session (10 male and 10 female aged 18-25 years; Jones et al, 2003). Participants rated each image on a 7-point Likert scale (eg, 'very unattractive' to 'very attractive').…”
Section: Behavioral Measuresmentioning
confidence: 99%